2020
DOI: 10.18203/2320-6012.ijrms20201931
|View full text |Cite
|
Sign up to set email alerts
|

A two years study of histopathological spectrum of skin adnexal tumors in a tertiary care centre of Southern Assam, India

Abstract: Background: Skin adnexal tumors (SAT) encompass a wide spectrum of benign and malignant tumors that differentiate toward one or more adnexal structures found in normal skin. Overall incidence of SATs is low yet they can be challenging to diagnose. Our study aims at analysis of histopathological spectrum of various SATs according to age, sex and anatomic locations along with histopathological features.Methods: It was a retrospective cross-sectional study conducted over a period of 2 years from June 2017 to May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A further factor contributing to the differences in our data is likely to be our exclusion of sebaceous naevi, which are now recognized to be a birthmark arising as a result of genetic postzygotic mosaicism in HRAS and KRAS , 34 and sebaceous hyperplasia; both case types are no longer included in the 2018 WHO classification of skin tumours 1,5,10 . In contrast, the prior literature (Table S4) typically included these cases in their analyses, which contributed to 4–47·9% of their cases 3,9,12,13,16–20,22,23,25–29,33 . The largest of these studies had a cohort of 1014 patients, and a significant proportion of these patients had cases that were of sebaceous differentiation (53%, 536 of 1014), the majority of which were sebaceous naevi and sebaceous hyperplasia (413 and 73, respectively) 9 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A further factor contributing to the differences in our data is likely to be our exclusion of sebaceous naevi, which are now recognized to be a birthmark arising as a result of genetic postzygotic mosaicism in HRAS and KRAS , 34 and sebaceous hyperplasia; both case types are no longer included in the 2018 WHO classification of skin tumours 1,5,10 . In contrast, the prior literature (Table S4) typically included these cases in their analyses, which contributed to 4–47·9% of their cases 3,9,12,13,16–20,22,23,25–29,33 . The largest of these studies had a cohort of 1014 patients, and a significant proportion of these patients had cases that were of sebaceous differentiation (53%, 536 of 1014), the majority of which were sebaceous naevi and sebaceous hyperplasia (413 and 73, respectively) 9 .…”
Section: Discussionmentioning
confidence: 93%
“…We found the most common benign SAT in adults to be hidrocystoma, followed by pilomatrixoma, trichilemmoma, cylindroma and spiradenoma. In the published literature, the most frequent tumours have been pilomatrixomas (11 of 24 studies), 12,14,17,19,21,[24][25][26][31][32][33] with hidradenomas (six of 24 studies) 13,15,20,24,27,30 also being frequently observed. We also analysed paediatric tumours (in patients aged ≤ 18 years), and found that they accounted for 10% of our caseload.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in concordance with that of Suri et al ( 6), Kaur et al (7), and El Ochi et al (10). Other authors (5,(11)(12)(13)(14)(15)(16) have reported sweat gland tumors to be the most common, followed by hair follicle tumors. Interestingly, Kamyab Hesari et al (4) found sebaceous tumors to be the most frequent type, which is unlike of most published studies.…”
Section: Discussionmentioning
confidence: 98%
“…As for gender, many published papers have documented (4,7,9,11,12,15) that both sexes are roughly equally affected. Some authors have described a slightly higher preponderance of males (6,10,17), while others have reported a mild predominance of females (5,13,14,16). These discrepancies must have been related to disparate proportions of histologic types of tumors in the study cohorts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation